Investigation of the chemical structure and formation mechanism of polydopamine from self‐assembly of dopamine by liquid chromatography/mass spectrometry coupled with isotope‐labelling techniques. (27th February 2019) - Chan, Wan
Abstract : Rationale: Dopamine (Dp) is one of the neurotransmitters released by the brain, and it was recently observed to undergo "self‐polymerization" to form polydopamine (polyDp) functional materials, with a poorly understood polymerization mechanism. In this study, we investigated the chemical structure of polyDp as well as the mechanism of its formation using a combination of mass spectrometric techniques for both liquid and solid‐state samples. Methods: Using the classical combustion analyses in combination with liquid chromatography coupled with spectrophotometric and mass spectrometric (MS) techniques and a 'bottom up' approach, we identified the major monomer units and a spectrum of oligomeric aggregates in the reaction mixtures of self‐assembling Dp. Furthermore, the effect of the reaction medium on the structure and composition of polyDp materials was also investigated using time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS) analysis. Results: A study of the MS and MS/MS spectra revealed for the first time that polyDp is partially composed of non‐covalent supramolecular aggregates with unmodified Dp (3, 4‐dihydroxyphenethylamine) and oxidized Dp (dopaminechrome) as the main building blocks. This finding was further validated via a heavy isotope labelling method and a 'top‐down' approach in which we detected Dp and dopaminechrome monomers in the synthesized polyDp material. To the best of our knowledge, this study provides the first direct evidence demonstrating the formation mechanism and chemical structure of polyDp. Conclusions: It is anticipated that the knowledge generated from this study will provide insight into the structure–property relationship of polyDp and assist in developing polyDp‐based material with better performance.